FUNGSI SEKSUAL PADA PRIMIPARA PASCA PERSALINAN PERVAGINAM DIBANDINGKAN DENGAN PRIMIPARA PASCA SEKSIO SESAREA - Erick Caesarrani Asmara (LPPM Universitas Abdurrab, 2022)
Sexual function is a fundamental component of life and plays an important role in marital stability. The focus is not only on physical sexual functioning but also on how individuals' needs can be met and satisfied by their physical, emotional, and social experiences with sex. Postpartum is a major transitional period for parents. Type of delivery and perineal trauma and pain during delivery are associated with sexual problems. This study was conducted to compare sexual function in primiparas after vaginal delivery with primiparas after cesarean section. This research uses Observational Analytic method with Cross-Sectional design. The research subjects were 60 postpartum primiparas at Binakasih Hospital in Pekanbaru during the period January - December 2020, who met the inclusion criteria. Subjects were divided into groups of primiparas after normal delivery and primiparas after cesarean section. The data that has been collected was analyzed by independent t-test. The results of the study showed that the average sexual function index value in primiparas after vaginal delivery was 24.81 and the average sexual function index value in primiparas after cesarean section was 27.59. There was a significant difference in the outcome of sexual function in primiparas after vaginal delivery and primiparas after cesarean section (p=0.010). Outcomes of sexual function in primiparas after cesarean section were significantly better than primiparas after vaginal delivery